VD_FINDINFO Jug / 2016 / 52 vom 5. Oktober 2015 - VD Tribunal cantonal (2015)
LÉSION CORPORELLE SIMPLE, VOIES DE FAIT, PARTIE CIVILE, TORT MORAL, FIXATION DE LA PEINE | 47 CO, 123 CP, 126 CP, 47 CP, 126 CPP (CH)